Declining joint family and emerging crisis in old age security. (11th July 2007) - Vaidyanathan, R.
The ageing India combined with a declining joint family system faces a crisis in social security for elderly. The government pension system has been converted from a defined benefit system to a Defined Contribution one. The mandatory schemes like Employees' Provident Funds Schemes cover a relatively small segment of the total work force. In all, more than 80% of the work force is not covered by any mandatory retirement/social security schemes. It is required for India to think of innovative products and systems to deal with the issues. Reverse mortgage on housing stock and converting huge stock of gold held by households by single premium pension products may help to some extent. But, it is equally important to stress on family values and savings based life style to face the long-term implications of the emerging crisis in the social security scene.